Private dwelling : contemplating the use of housing - King, Peter, 1960-2023. (London ; New York, NY : Routledge, 2004)
This book considers the personal and subjective use of housing and the ways we use our housing, as well as discussion of a method for analysing these actions.
What is dwelling? -- Privacy : when dwelling closes in on itself -- A brick box or a velvet case? -- Talking about houses -- Ripples : sharing, learning, reaching out -- Want it, have it! -- Fear and the comfort of the mundane -- Loss.
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: Housing; Housing -- Psychological aspects; Functionalism (Social sciences); Fonctionnalisme (Sciences sociales); SOCIAL SCIENCE -- General; BUSINESS & ECONOMICS -- Infrastructure; Functionalism (Social sciences); Housing; Housing -- Psychological aspects